2009
DOI: 10.1002/hep.23008
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulated microRNA‐143 transcribed by nuclear factor kappa B enhances hepatocarcinoma metastasis by repressing fibronectin expression†

Abstract: It is increasingly clear that hepatocellular carcinoma (HCC) has a distinct microRNA (miRNA) expression profile that is involved in malignancy; however, little is known about how functional miRNA modulates the metastasis of hepatitis B virus (HBV)-related HCC (HBV-HCC). In the present study, we demonstrate that the levels of miRNA-143 (miR-143) are dramatically increased in metastatic HBV-HCC of both p21-HBx transgenic mice and HCC patients. Moreover, we show that overexpression of this miRNA is transcribed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
256
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 339 publications
(271 citation statements)
references
References 32 publications
11
256
1
3
Order By: Relevance
“…It has been reported that miR-143 is downexpressed in colon (15), lung (16) and prostate cancer (17) and is overexpressed in hepatocarcinoma (18). Furthermore, miR-143 is involved in the regulation of MYO6 expression in prostate cancer (17); extracellular signal-regulated kinase-5 (ERK-5) is a miR-143 target in prostate cancer and miR-143 inhibits the proliferation at least in part by the inhibition of ERK-5 activity (19).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR-143 is downexpressed in colon (15), lung (16) and prostate cancer (17) and is overexpressed in hepatocarcinoma (18). Furthermore, miR-143 is involved in the regulation of MYO6 expression in prostate cancer (17); extracellular signal-regulated kinase-5 (ERK-5) is a miR-143 target in prostate cancer and miR-143 inhibits the proliferation at least in part by the inhibition of ERK-5 activity (19).…”
Section: Discussionmentioning
confidence: 99%
“…After overnight fixation at 4°C, the tissue was dehydrated and paraffin embedded, cut into 5-m sections, stained with hemotoxylin and eosin, and examined with light microscopy. 15,16 We performed radial alveolar counts, as previously described. 17 From the center of the respiratory bronchiole, a perpendicular line is drawn to the edge of the acinus, and the number of the septa intersected by that line are counted.…”
Section: Histologymentioning
confidence: 99%
“…This is the first study to demonstrate that HBx/nuclear factor B(NF-B)/mir-143/fibronectin type III domain containing 3B (FNDC3B) is an important signal pathway in pathological process of HCC metastasis. 1 Yet, we still have several questions about this study.…”
mentioning
confidence: 94%